Overcoming Fraud and Cybercrime: The Role of Integrity in Village Financial System Reporting - Nabilla Azzahra Dwi Ningrum; Kristina Devihanna Batubara; Aprina Nugrahesthy Sulistya Hapsari (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
This research aims to describe the implementation of control in village financial system (Indonesia: Sistim Keuangan Desa / Siskeudes) in order to maintain the integrity data of village funds, outright the monitoring againsts the threat of fraud, both in a form of conventional and also cybercrime. The technique used in this research is descriptive qualitative methods and the data used are primary data obtained from direct interviews with the key person informants and the secondary data in the form of documentation to support this research as evidence of the controls to be identified. Results shows that Internal Control such as Environmental Control, Physical Security Control, Logical Security Control and IS Operating Control has been implemented in Siskeudes Samirono. If all the control is being optimally implemented and periodically reviewed to ensure that it is able to mitigate the risk of fraud and cybercrime in the implementation of Siskeudes, the quality of the information produced will be ensured.